2013
DOI: 10.1111/ahg.12024
|View full text |Cite
|
Sign up to set email alerts
|

Wilson Disease Mutation Pattern with Genotype‐Phenotype Correlations from Western India: Confirmation of p.C271* as a Common Indian Mutation and Identification of 14 Novel Mutations

Abstract: SummaryWilson disease (WD) is an autosomal recessive disorder resulting from mutations in the ATP7B gene, with over 600 mutations described. Identification of mutations has made genetic diagnosis of WD feasible in many countries. The heterogeneity of ATP7B mutants is, however, yet to be identified in the Indian population. We analyzed the mutational pattern of WD in a large region of Western India. We studied patients (n = 52) for ATP7B gene mutations in a cohort of families with WD and also in first-degree re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 27 publications
5
55
2
Order By: Relevance
“…Three mutations including, c.2865+1G>A, p.(Trp1153Arg), and novel mutation p.(Asp642Tyr) were found to affect all the siblings of three different families, indicating their sporadic distribution. While c.2865+1G>A is a rare mutation having one incidence each from the Czech Republic and Western India (1%) (Aggarwal et al., ; Vrabelova, Letocha, Borsky, & Kozak, ), p.(Trp1153Arg), present in the European population (Waldenström, Lagerkvist, Dahlman, Westermark, & Landegren, ), is the first time being reported from India in this study. The missense mutation, p.(Ala1003Thr) (3%) and the frameshift mutation exclusive to India, p.(Thr1050Hisfs*71) (1%), affected similar proportions of patients in this study to that of previously reported studies (Aggarwal et al., ; Gupta et al., ; Kumar et al., ), indicating their overall low frequency in India.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Three mutations including, c.2865+1G>A, p.(Trp1153Arg), and novel mutation p.(Asp642Tyr) were found to affect all the siblings of three different families, indicating their sporadic distribution. While c.2865+1G>A is a rare mutation having one incidence each from the Czech Republic and Western India (1%) (Aggarwal et al., ; Vrabelova, Letocha, Borsky, & Kozak, ), p.(Trp1153Arg), present in the European population (Waldenström, Lagerkvist, Dahlman, Westermark, & Landegren, ), is the first time being reported from India in this study. The missense mutation, p.(Ala1003Thr) (3%) and the frameshift mutation exclusive to India, p.(Thr1050Hisfs*71) (1%), affected similar proportions of patients in this study to that of previously reported studies (Aggarwal et al., ; Gupta et al., ; Kumar et al., ), indicating their overall low frequency in India.…”
Section: Discussionmentioning
confidence: 48%
“…The p.(His1069Gln), the most common mutation in European pedigree affecting 30–70% WD population, is absent in the Indian population (Gomes et al., ; Kumar et al., ). The p.(Cys271*) mutation has been reported to affect 11–20% WD population in India (Aggarwal et al., ; Gupta et al., ; Santhosh et al., ). In agreement with earlier studies, our investigation too revealed a 10% frequency of p.(Cys271*) in this region of India, which indicates that it is a common mutation in India and can be screened first in Indian WD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PCR products were cloned into plasmid pCR2.1-TOPO (TOPO TA Cloning kit; Invitrogen). For sequence determination of ATP7B established protocols were used [19].…”
Section: Methodsmentioning
confidence: 99%
“…The Cys271Stop was the most common mutation observed in Western India with an allelic frequency of 20.2%. [77] It was observed from four population of India that the missense mutations account for 44% of the total mutations followed by insertion and deletion mutations.…”
Section: Mutations Were Identified From North and Southmentioning
confidence: 99%